Effect of Natural Feeds on The Growth Performance, Survival Rate and Feed Utilization of the Tropical Shortfin Eel Anguilla bicolor McClelland 1844 (Pisces: Anguillidae) Larvae - Yanti, Riska Zulinda; Muchlisin, Zainal A.; Nur, Firman M; Irham, Muhammad; Batubara, Agung S.; Muhammadar, Abdullah A.; Fadli, Nur (Polish Journal of Natural Sciences, 2023)
The high mortality of eels larvae has commonly occurred during the acclimatization process prior to growing, this is probably due to the unsuitable feed intake. Therefore, the aim of the study was to find suitable natural feed for tropical shortfin eel Anguilla bicolor larvae. The research was performed at the Syiah Kuala University, Indonesia from April to June 2017. The complete randomized experimental design with four treatments and four replications were utilized in present study. Four natural feeds were tested, namely: bloodworm Tubifex sp., golden apple snail Pomacea canaliculata, sardine fish Decaptersus macarellus and ebi-shrimp Euphausia sp. The average of total length and body weight of the eel larvea sample were of 6.0 cm and 0.15 g, respectively. The experimental fish was reared at density of 10 fish tank-1. The eel larvea were raised in plastic containers volume 22 L. The experimental fish fed on natural feeds at feeding ration of 10% body weight a day for 60 days. The results revealed that the natural feeds gave the significant effect on weight gain, specific growth rate, survival rate, feed efficiency and feed conversion ratio (P <0.05). The fish fed on sardineresulted in a better results compared to other tested feeds, but the values were not different significantly with bloodworm. It is concluded that sardine fish and bloodworm are suitable for eel A. bicolor larvae.